Literature Review: The Effect of Science, Technology Engineering, Arts, and Mathematics (STEAM)-Based LKPD to Improve Learners Creativity in Physics Learning - Indri Maya Ariana; Binar Kurnia Prahani; Dwikoranto Dwikoranto; Muhammed Akif Kurtuluş (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2025)
Objective: So far, students are limited by the use of teaching materials such as package books or textbooks as one of the available learning resources. The main problem that arises is the lack of availability of STEAM-oriented Learner Worksheet teaching materials that can arouse students' creativity. This research aims to conduct a literature review related to the effect of science, technology, engineering, arts, and mathematics (STEAM)-based Worksheet to improve students' creativity in physics learning. Method: The research method used is literature review or literature study. The secondary data used in this study came from national and international articles indexed by Google Scholar, DOAJ, and Scopus totaling 21 articles with a time span of 2019 to 2024. Results: From this research, it is concluded that, showing that the Science, Technology, Engineering, Arts, and Mathematics (STEAM)-based Learner Worksheet has a significant effect on increasing student creativity in physics learning. STEAM-based Worksheet is considered valid, practical, and effective in supporting 21st century learning that involves critical thinking, creativity, problem solving, and collaboration. Novelty: Thus, the use of STEAM methods in education, especially through the development of STEAM-oriented Learner Worksheets in Indonesia, continues to show a positive impact in improving students' critical thinking and creative thinking skills, as well as strengthening science and technology literacy.